Clinical Pastoral Counseling: An Australian Model - Sotheren, Douglas I. (The Journal of pastoral care, 1983)
Describes a model of clinical pastoral counseling developed in a rural area of Australia. Levels of functions in the model include those of pastoral care, pastoral counseling, clinical pastoral counselor, and psychotherapist. Notes the tensions between evangelical theology and humanistic therapy and how these are expressed in supervision.